(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the key features of the assessment mechanisms in the Finnish education system and their impact on students’ personal development, critical thinking, and creativity. It also explores ways to adapt the Finnish assessment model to Uzbekistan’s general secondary education system, emphasizing the integration of diagnostic, formative, and summative assessment elements and the teacher’s role as a facilitator rather than an evaluator. The findings highlight the practical importance of implementing innovative assessment approaches to enhance student motivation and improve education quality in.